Diversity, Distribution, and Evolution of Bioluminescent Fungi - Brian A. Perry; Dennis E. Desjardin; Cassius V. Stevani (Journal of Fungi)
All known bioluminescent fungi are basidiomycetes belonging to the Agaricales. They emit 520–530 nm wavelength light 24 h per day in a circadian rhythm. The number of known bioluminescent fungi has more than doubled in the past 15 years from 64 to 132 species. We currently recognize five distinct lineages of bioluminescent Agaricales belonging to the Omphalotaceae (18 species), Physalacriaceae (14), Mycenaceae (96), Lucentipes lineage (3), and Cyphellopsidaceae (1). They are distributed across the globe with the highest diversity occurring on woody or leafy substrates in subtropical closed canopy forests with high plant diversity. With the caveat that most regions of the world have not been extensively sampled for bioluminescent fungi, the areas with the most known species are Japan (36), South America (30), North America (27), Malesia, South Asia, and Southeast Asia (26), Europe (23), Central America (21), China (13), Africa (10), Australasia, Papua New Guinea, and New Caledonia (11), and the Pacific Islands (5). Recent studies have elucidated the biochemical and genetic pathways of fungal bioluminescence and suggest the phenomenon originated a single time early in the evolution of the Agaricales. Multiple independent evolutionary losses explain the absence of luminescence in many species found within the five lineages and in the majority of Agaricales.